Impact of Transformational Leadership Style On Secondary School Students’ Academic Achievement in Mbeere South Sub-County, Embu County, Kenya - Kimiti, Richard Peter; Mwinzi, Kathamba Archippus (My University, 2016)
Globally, education is considered as the key drive of any country’s development. This explains the reason why academic achievement is given a lot of importance in the schooling process. In this respect and specifically in the developing countries, many researchers have focused on curriculum factors that may lead to better academic achievement. The influence of human resource on academic achievement though widely researched has not exhaustively addressed the significant role played by the school managers on student’s academic achievement. The purpose of this study was therefore to establish the impact transformational leadership style on academic achievement in secondary schools in Mbeere South Sub-County, Embu County, Kenya. The research adopted a descriptive survey study design. Thirty four (34) secondary schools were sampled for the study. The simple random sampling technique was used to select a sampling matrix of 340 respondents comprising of 34 principals, 240 teachers and 66 non-teaching staff. The data collected was processed and analyzed by use of Statistical Package for Social Sciences (SPSS). Both qualitative and quantitative data analysis methods were applied in this study. The findings were presented by use of frequencies, tables, graphs and pie-charts. The results of the study showed that apart from transformational leadership style, democratic and autocratic leadership styles were also used in secondary schools in Mbeere Sub-County. The findings of the study further revealed the principals who adopted transformational leadership significantly improved academic achievement of their secondary school students. Based on these findings, it is recommended that to the school administrators should adopted leadership styles that are more employee friendly but which are results oriented.
Keywords: Academic achievement; Leadership style; Transformational leadership